A Modified NK Cell Degranulation Assay Applicable for Routine Evaluation of NK Cell Function - Snehal Shabrish; Maya Gupta; Manisha Madkaikar (Journal of Immunology Research)
Natural killer (NK) cells play important role in innate immunity against tumors and viral infections. Studies show that lysosome-associated membrane protein-1 (LAMP-1, CD107a) is a marker for degranulation of NK and cytotoxic T cells and its expression is a sensitive marker for the cytotoxic activity determination. The conventional methods of determination of CD107a on NK cells involve use of peripheral blood mononuclear cells (PBMC) or pure NK cells and K562 cells as stimulants. Thus, it requires large volume of blood sample which is usually difficult to obtain in pediatric patients and patients with cytopenia and also requires specialized laboratory for maintaining cell line. We have designed a flow cytometric assay to determine CD107a on NK cells using whole blood, eliminating the need for isolation of PBMC or isolate NK cells. This assay uses phorbol-12-myristate-13-acetate (PMA) and calcium ionophore (Ca2+-ionophore) instead of K562 cells for stimulation and thus does not require specialized cell culture laboratory. CD107a expression on NK cells using modified NK cell degranulation assay compared to the conventional assay was significantly elevated (p<0.0001). It was also validated by testing patients diagnosed with familial hemophagocytic lymphohistiocytosis (FHL) with defect in exocytosis. This assay is rapid, cost effective, and reproducible and requires significantly less volume of blood which is important for clinical evaluation of NK cells.